Epidemiological Study of Scorpion Sting in Lordegan City during the Years 2014- 2017 - Masoud Amiri; mehdi Naderi Lordjani; Hasan Asgarpour (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Scorpion bite is one of the major health problems in most countries. Lordegan is one of the areas where several reports of Scorpion bite occur. The purpose of this study was to describe the epidemiological and demographic characteristics of selected scorpions for preventive measures. Methods: This descriptive cross-sectional study was conducted to collect information about all the scorpion patients in Lordegan city health center during 92-95. Results: The results showed that the total number of scorpion scourges was 2422, of which 1124 cases were female (46.4%) and 1298 cases were male (53.6%).of the total bite, 2 deaths occurred. Death rate The disease in this area is about .01 % In 1000 people, 2060 cases were rural (85.1%) and 362 were urban (14.9%). 764 (31.5%) were less than 1 hour and 30 minutes, and 749 people (31%) were between 1 hour and 30 minutes to 3 Hours and 909 people (37.5%) visited more than three hours. Bites in the body organs included (39% leg , 35% hands, 20% trunk, 6% head and neck). (99.9%) Improvement , and (.01%) Death , most bites are from April To the month of October. Most of the age group had bites of 15 to 24 years old and the lowest bites were in the age group of 65 and older. 80.6% of bites were scorpions by yellow scorpions and 19.4% by scorpions. Conclusion: Scorpio bites are common in Lordegan, especially in the heat season, thus informing and educating the general public and individual protection can prevent scorpion bites.